Identification Of Quantitative Characters of Two Pineapple Varieties (Ananas comosus L. Merr) Resulted By Propagation Of Stem Cutting In Okinawa Prefecture - Laela Maulida; Ni Wayan Sri Suliartini; I Wayan Sudika (Jurnal Biologi Tropis, 2023)
Pineapple (Ananas comosus L. Merr) is one of the significant yields and the fundamental product created in Okinawa since it is appropriate climatic condition for pineapple improvement. seeds. This study intends to decide the quantitative characters of seedlings from stem engendering of pineapple (Ananas comosus L. Merr) stem cutting on two assortments in Okinawa, Japan. The review was led in December 2022 at Yagaji Island Nursery, Okinawa, Japan. A quantitative descriptive approach was used in the research, and random sampling was used to select 15 seedlings from each variety based on their age, starting at 60 HST, 90 HST, and 120 HST, for a total of 90 samples. Each seed test was noticed in view of boundaries set each month, in particular seedlding level, stem width number of leaves and. Research information were dissected utilizing basic measurement examination. The mean of each character was tried utilizing the T-test at the 5% level and the connection between's qualities was broke down utilizing the r-test at the 5% level. The outcomes showed that there were contrasts in quantitative characters of the two assortments, specifically the N67-10 assortment showing taller seedlings, more number of leaves and bigger stem at the three periods of perception, with the exception of 60 days for stem distance across and 120 days for seedling level. With a range of 0.44-0.77, the phenotypic correlation between characters is real.